Electrical storm – still an extremely poor prognosis. Do these acute states of life-threatening arrhythmias require a multidirectional approach from the start? - Gadula-Gacek, Elżbieta; Tajstra, Mateusz; Gąsior, Mariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2019)
Electrical storm (ES) is a state of electrical instability of the heart manifesting as multiple and potentially lethal recurring ventricular arrhythmias such as ventricular tachycardia or ventricular fibrillation. This definition is not related to the condition of each patient, who can present from asymptomatic to unconscious and in deep cardiogenic shock. Most patients affected by ES have heart failure (HF) of ischaemic origin. Ischaemia, exacerbation of HF, low ejection fraction, previous ventricular arrhythmias, infection or electrolyte disturbances together with other factors, or a few factors combined, may result in ES. The prognosis of ES survivors is very poor, with 1-year mortality exceeding 40%, which should draw attention to this group of patients as one of extremely high risk. The number of patients with cardioverter-defibrillators is increasing and so is the number of patients suffering from ES. Therefore, each patient should be supported with tailored therapy, and not only restricted to pharmacotherapy or ablation procedures. This paper was written to analyse the most frequent causes of ES and prompt the most appropriate clinical pathways and possibilities, underlining the need for a comprehensive invasive approach to diagnosis, treatment and circulatory stabilization in addition to adequate pharmacotherapy. This approach might help to reduce the mortality rate in this group of patients and improve the prognosis.